COMPARISON OF MUSCLE ACTIVITIES BETWEEN BARBELL DEADLIFT AND JEFFERSON DEADLIFT - Moon, Byoung-Hyoun; Lim, Young-Jin; Kim, Ji-Won (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to identify changes in the muscle activity of the trunk and lower extremity during barbell deadlift and Jefferson deadlift. Methods/Statistical analysis: 24 people (14 male and 10 female) were selected to measure the muscle activity of the erector spinae, gluteus maximus, rectus femoris and rectus abdominis. Paired t-test was conducted to determine the difference in muscle activity during barbell deadlift and jefferson deadlift. Statistical programs used SPSS Version 22.0 (Statistics Package for the Social Science). Findings: There were significant differences in rectus femoris and elector spinae during barbell deadlift and jefferson deadlift. Rectus femoris showed higher muscle activity in jefferson deadlift than barbell deadlift in the ascending phase and deccending phase (P>.05). Erector spinae showed higher muscle activity barbell deadlift than jefferson deadlift in the all phase (P>.05). Improvements/Applications: This study suggests that jefferson deadlift is effective to increase muscle activity of RF with decrease muscle activity of ES than barbell deadlift.